ROBDD-TrOCRBERTa: a novel robust-optimized blurred document text deblurring and completion with DCGAN-TrOCR and DistilRoBERTa - Ranjan, Arti; Ravinder, M. (International journal of information technology (Singapore. Online), 2024)
Blurred text documents such as historical documents, handwritten manuscripts, old newspapers, moist invoices or legal agreements, old books, hand written notes often present readability challenges because the quality of the text has deteriorated over time. The proposed Robust Optimized Blurred Document Text Deblurring and Text Recognition (ROBDD-TrOCRBERTa) method tackles the challenge of improving readability in deteriorated text documents such as historical documents, handwritten manuscripts, and old newspapers. This innovative approach is divided into two phases. First, it employs Deblurring using DCGAN to enhance image quality by reducing noise and blurriness. Subsequently, it leverages TrOCR integrated with DistilRoBERTa for efficient text recognition and completion. Experimental results show that this method is effective in various real-world scenarios, making it a promising solution for automated document analysis and digitization in challenging conditions.